Analisis Yuridis terhadap Pertanggungjawaban Pengelolaan Keuangan Desa oleh Kepala Desa berdasarkan Undang-undang Nomor 3 Tahun 2024 tentang Desa - Ni Putu Astini; Erikson Sihotang; A.A. Gde Putra Arjawa (PT. PENERBIT TIGA MUTIARA, 2025)
The enactment of Law Number 3 of 2024, as the second amendment to Law Number 6 of 2014 concerning Villages, has introduced new challenges in the governance of village administration, particularly in the legal accountability of village heads in managing village finances. Although the law outlines the authority of village heads, it does not explicitly stipulate provisions for criminal or civil sanctions in cases of abuse of power. This normative gap poses potential risks of harm to village communities due to the weak legal accountability mechanisms. This study aims to examine and analyze the legal implications of the normative vacuum in village regulations and to emphasize the urgency of establishing more specific and binding implementing regulations. Employing a normative juridical research method through statutory and conceptual approaches, this study analyzes relevant legislation and supporting legal literature. The findings reveal that the absence of clear legal sanction provisions in the Village Law creates a legal grey area that can be exploited for administrative misconduct and corruption. Therefore, regulatory reform is required in the form of amendments or the formulation of implementing regulations that explicitly define the types of sanctions and legal accountability mechanisms for village heads. The novelty of this study lies in its systematic identification of legal loopholes that have received limited attention in existing village law literature, as well as its concrete proposals for regulatory reformulation aimed at strengthening accountability and transparency in village financial management.